Insect wars - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The hibiscus cochineal insect (Maconellicoccus hirsutus), a native of Asia, has been invading the Caribbean, the southern part of the United States and the north of Latin America (including Guyana) since 1994. It has wrought massive damage to plants...